BUSINESS INTELLIGENCE ANALYSIS IN THE IMPLEMENTATION OF DIGITAL TICKETING SYSTEM TO IMPROVE EFFICIENCY AND ACCESSIBILITY IN ANCOL - Prameswari, Diana; Faeni, Dewi Puspaningtyas (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The COVID-19 pandemic has provided additional challenges for Taman Impian Jaya Ancol Tbk, especially in the field of ticketing and visitor management. This paper discusses how to implement the Ancol Tourism Management Information System. The application of business intelligence is becoming increasingly important to analyze visit trends and respond to changes in consumer behavior. In this context, business intelligence plays an important role in enriching management information systems by providing more in-depth analytical information and strategic insights. The business intelligence business architecture in e-commerce information systems provides a more dynamic and responsive environment to modern business needs. The paper also discusses the importance of the use of the Intelligence Business Architecture in E-Commerce information systems.